2005
DOI: 10.1093/jac/dki354
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual variability of once-daily ritonavir boosted saquinavir pharmacokinetics in Thai and UK patients

Abstract: The ritonavir AUC and study site appeared to be related to exposure of saquinavir. Study site should be viewed as the total of country- and study-specific differences--such as differences in lifestyle, environment, genetic background and dietary composition--between the analysed studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
4
17
2
Order By: Relevance
“…In addition, the SQV AUC 0-24 values in our patients were Ͼ20,000 ng/ml ⅐ h, the cutoff at which 85% of the maximum antiviral effect is expected in patients without protease gene mutations (17,18). The observed interindividual variability in SQV concentrations, both in plasma and intracellularly, was considerable, although within the range of other studies on SQV and other PIs (3,4,5,6,7,11,13,17,19,21,25,26,30,31,34).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, the SQV AUC 0-24 values in our patients were Ͼ20,000 ng/ml ⅐ h, the cutoff at which 85% of the maximum antiviral effect is expected in patients without protease gene mutations (17,18). The observed interindividual variability in SQV concentrations, both in plasma and intracellularly, was considerable, although within the range of other studies on SQV and other PIs (3,4,5,6,7,11,13,17,19,21,25,26,30,31,34).…”
Section: Discussionsupporting
confidence: 72%
“…Patients were instructed to always take SQVr in the morning, after a highly caloric breakfast. Pharmacokinetic data were obtained from 103 unselected patients; for 26 of these patients, we obtained a 24-h pharmacokinetic profile with blood samples collected predose (baseline) and at 2,4,6,8,12, and 24 h after a supervised drug intake, whereas from each of the remaining 77 patients a single sample was withdrawn at 24 Ϯ 0.5 h postdose (C min ). The pharmacokinetic studies were performed at steady state, once the patients had been on treatment for at least 1 month.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were initially treated with the soft-gel formulation of SQV and switched to the film-coated formulation during the study, with 95.7% of patients achieving HIV-1 RNA <50 copies/ml at 40 weeks. The higher response in this study may reflect the difference in race between the study populations, which has been shown to affect SQV pharmacokinetics [20]. Importantly, the proportion of patients with HIV-1 RNA <50 copies/ml at 48 weeks was maintained for up to 96 weeks in the study by Ananworanich et al, demonstrating the durability of response to SQV/r [13].…”
Section: Discussionmentioning
confidence: 85%
“…In humans, the minimum recommended effective concentration for SQV is 0.1 mg/L in serum, and treatment combining 1600 mg SQV and 100 mg ritonavir once daily can produce a maximum concentration (C max ) of 0.98-12.36 mg/L and a mean area under the curve (AUC) of 17.88-67.05 mg·h/L for SQV-depending on body weight, gender, and study site (Autar et al, 2005). SQV has also been used in HIV patients without ritonavir (Sarmati et al, 1997).…”
Section: Animals and Animal Exposurementioning
confidence: 99%